The role of tourism in economic growth: Empirical evidence from Saudi Arabia - Sana Naseem (Economies, 2021)
Tourism is vital to the success of many economies worldwide and has been a widely researched area for many years. Unfortunately, an insufficient number of studies have been conducted on this subject in the context of Saudi Arabia. Therefore, this research investigates the role of tourism in promoting economic growth in the Kingdom of Saudi Arabia by using annual time series data from 2003 to 2019. The study uses basic statistics, correlation coefficients, the unit root test, the Johansen co-integration test, the co-integration regression test and the Granger causality test to check the relationship between tourism and economic growth. The results show that economic growth has a long-run relationship with tourism receipts, tourism expenditures and the number of tourist arrivals; the number of tourist arrivals has a strong relationship with economic growth, compared to other parameters. The empirical results validate the concept that tourism promotes economic growth in the kingdom of Saudi Arabia.
Keywords: C01; F41; F43; O53; 330; economic growth; Saudi Arabia; tourism